CLINICAL OUTCOME USING MODIFIED LATERAL TARSAL STRIP AND RESCESS LEVATOR IN PATIENTS WITH OCULAR PROBLEM DUE TO FACIAL NERVE PALSY: Poster Presentation - Case Report - Resident - RIF’AT NURFAHRI; Ratna Doemilah (Majalah Oftalmologi Indonesia, 2023)
Introduction : Facial nerve palsy is a condition that affects various organ including the eyes. We report a case of facial nerve palsy with eye manifestations in one patient that requires immediate action to save the cornea. Case Illustration : A 63-year-old male presented to our OPC with the primary complaint of right eyelid inability to close since September 2021after brainstem tumor excision, which had worsened since May 2022. Visual acuity: 2 meters counting fingers; IOP: 11 mmHg. Anterior segment examination revealed lagophthalmos (8 mm) in the right eye, a pinch test result of 10mm (horizontal laxity), conjunctival hyperemia, conjunctivalization of the cornea, a fluorescein test result of 7 x 4 mm, and band keratopathy. The wrinkles on the patient's right face disappeared. There was numbness, and the smile was asymmetrical. Patient underwent right eye modified lateral tarsal strip and recesses levator 8mm. The patient's eyelids can close tightly almost symmetrically with the left eye and no ptosis after operations. One week after operation, patient feels more comfortable, and the conditionof the cornea has improved. The facial nerve is vulnerable to trauma because of its path from the brainstem through the temporal bone to the facial muscles. In conditions of irreversible facial nerve palsy, managements are focus to overcome the complications. Modified lateral tarsal strips and levator recesses are relatively simple and inexpensive techniques that can help to overcome lagophthalmos. Discussion : Conclusion : Ocular manifestations can occur in patients with facial nerve paresis. Modified lateral tarsal strips and recesses levator eyelids can help protect the cornea.